Study on the Anti-inflammatory and Antioxidant Effects of Sipyungtang - Na Young Jo; Eun Yong Lee; Jeong Du Roh; Cham Kyul Lee (Journal of Acupuncture Research)
Background: The present study aimed to investigate the anti-inflammatory and antioxidant effects of Sipyungtang using lipopolysaccharide (LPS)-treated RAW 264.7 cells. Methods: Cell viability was measured using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromided (MTT) assay (Bio Basic). RAW 264.7 cells were cultured and treated with LPS to verify the inhibitory effects of Sipyungtang on nitric oxide (NO) production and cytokine generation and its antioxidant effect was assessed using 2,2-diphenyl-1-picrylhydrazyl. Results: Sipyungtang showed no cytotoxicity at concentrations of < 7.50 mg/mL. NO production was inhibited by Sipyungtang in a concentration-dependent manner, with the inhibitory effect observed at concentrations ranging from 0.47 mg/mL to 3.75 mg/mL. Regarding inhibiting cytokine production, interleukin (IL)-1β levels reduced markedly upon Sipyungtang treatment at concentrations of < 0.94 mg/mL, those of IL-6 at concentrations < 1.88 mg/mL, and tumor necrosis factor (TNF)-α at concentrations < 0.94 mg/mL. The antioxidant assay revealed that Sipyungtang exerted antioxidant effects ranging from 21.29% ± 1.72% to 72.20% ± 1.00% at concentrations ranging from 0.16 to 2.50 mg/mL. Conclusion: Our data indicate that Sipyungtang is safe, inhibits NO production, exhibits anti-inflammatory effects by reducing the production of cytokines IL-1β, IL-6, and TNF-α, and has antioxidant properties. Based on these findings, Sipyungtang may have potential applications in treating diseases caused by inflammation.